The Second of Two One-Year, Multicenter, Open-Label, Repeat-Dose, Phase II Safety Studies of PrabotulinumtoxinA for the Treatment of Moderate to Severe Glabellar Lines in Adult Patients. (3rd May 2021) - Lorenc, Z Paul; Adelglass, Jeffrey M; Avelar, Rui L; Baumann, Leslie; Beer, Kenneth R; Cohen, Joel L; Cox, Sue Ellen; Dayan, Steven H; Dover, Jeffrey S; Downie, Jeanine B; Draelos, Zoe Diana; Goldman, Mitchel P; et al.
Abstract: Background: PrabotulinumtoxinA is a 900-kDa botulinum toxin type A produced by Clostridium botulinum . Objectives: The authors sought to investigate the safety of prabotulinumtoxinA for treatment of glabellar lines. Methods: This was a multicenter, open-label, repeat-dose, 1-year phase II safety study. Adults with moderate to severe glabellar lines at maximum frown, as independently assessed by both investigator and patient on the validated 4-point photonumeric Glabellar Line Scale (0 = no lines, 1 = mild, 2 = moderate, 3 = severe), were enrolled. On day 0, patients received an initial treatment (IT) of 20 U prabotulinumtoxinA (4 U/0.1 mL final vacuum-dried formulation injected into 5 glabellar sites). On and after day 90, patients received a repeat treatment (RT) if their Glabellar Line Scale score was ≥2 at maximum frown by investigator assessment. Safety outcomes were evaluated throughout the study. Results: The 570 study patients received a median total dose of 60 U, that is, 3 treatments. Sixty-one patients (10.7%) experienced adverse events (AEs) assessed as possibly study drug related; 6.5% experienced study drug–related AEs after the IT. With each RT, progressively lower percentages of patients experienced study drug–related AEs. Eight patients (1.4%) experienced study drug–related AEs of special interest: 5 experienced eyelid ptosis (0.9%), 3 eyebrow ptosis (0.5%), 1 blepharospasm (0.2%), and 1 blurred vision (0.2%). Seven patients (1.2%) experienced serious AEs, but none were study drug related. A total of 4060 serum samples were tested for antibotulinum toxin antibodies; no seroconversion was observed. Conclusions: The safety of RTs of 20 U of prabotulinumtoxinA for moderate to severe glabellar lines was confirmed in this second phase II study based on a broad range of outcomes. Level of Evidence: 2: